The economic environment and FDI flows in Africa: the role of corruption control - (:unkn) unknown (My University, 2024)
The objective of this paper is to analyse the impact of corruption control and the economic environment on foreign direct investment (FDI) flows to African middle-income countries over the period 2002-2022 (21 years). To examine this relationship, this paper uses the dynamic two-stage system GMM approach suggested by Blundell and Bond (1998). The results reveal that controlling corruption (휷ퟒ= 3.61) has a positive effect on FDI inflows. Indeed, a one-percentage point improvement in the control of corruption generates a 3.61% increase in FDI inflows in the context of African middle-income countries. In terms of macroeconomic indicators, only the variables GDP growth rate (휷ퟏ= 0.015) and trade openness (휷ퟑ= 0.046) have a positive and significant influence on the attractiveness of FDI. Inflation, on the other hand, has no significant effect. This proves that a healthy macroeconomy and effective control of corruption are essential for attracting FDI flows, which is another novelty of this study. These results constitute important empirical evidence for researchers, as well as for African economies to apply macroeconomic reforms and policies aimed at reducing corruption.
Keywords: African Research